2016
DOI: 10.1093/gbe/evw140
|View full text |Cite
|
Sign up to set email alerts
|

Species- and Strain-Specific Adaptation of the HSP70 Super Family in Pathogenic Trypanosomatids

Abstract: All eukaryotic genomes encode multiple members of the heat shock protein 70 (HSP70) family, which evolved distinctive structural and functional features in response to specific environmental constraints. Phylogenetic analysis of this protein family thus can inform on genetic and molecular mechanisms that drive species-specific environmental adaptation. Here we use the eukaryotic pathogen Leishmania spp. as a model system to investigate the evolution of the HSP70 protein family in an early-branching eukaryote t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 79 publications
(104 reference statements)
1
19
1
Order By: Relevance
“…Another gene—today annotated as cysteine leucine-rich protein (CLrP, LinJ.34.0570)—was revealed causing antimony resistance in L. tarentolae transfected with a cosmid library prepared from arsenite and SbIII resistant parasites (Brochu et al, 2004 ), and in L. infantum axenic amastigotes (Genest et al, 2008 ). Brochu et al also reported members of the HSP70 protein family as important genes contributing to antimony tolerance, supporting recent phylogenetic evidence that HSP70 family members may allow parasite environmental adaptation with potential important consequences for drug susceptibility (Drini et al, 2016 ).…”
Section: Cosmid-based Functional Genetic Screening In Leishmentioning
confidence: 64%
“…Another gene—today annotated as cysteine leucine-rich protein (CLrP, LinJ.34.0570)—was revealed causing antimony resistance in L. tarentolae transfected with a cosmid library prepared from arsenite and SbIII resistant parasites (Brochu et al, 2004 ), and in L. infantum axenic amastigotes (Genest et al, 2008 ). Brochu et al also reported members of the HSP70 protein family as important genes contributing to antimony tolerance, supporting recent phylogenetic evidence that HSP70 family members may allow parasite environmental adaptation with potential important consequences for drug susceptibility (Drini et al, 2016 ).…”
Section: Cosmid-based Functional Genetic Screening In Leishmentioning
confidence: 64%
“…Both spots were identified as LinJ30.2480 (Tritryp gene ID). This gene is a putative heat-shock 70-related protein 1 (mitochondrial precursor) with a predicted MW of 71.6 kDa (designated as HSPA9B [10]).
Fig. 12D-DIGE quantitative analysis of miltefosine-resistant L. donovani .
…”
Section: Resultsmentioning
confidence: 99%
“…Members of the HSP70 family localized in the mitochondria, such as HSPA9B, are most similar to the bacterial DnaK [13]. Moreover, in most organisms, ER and mitochondrial HSP70s are constituted by a sole protein, however an interrogation of the L. donovani genome revealed four HSPA9 genes (A-D) with minor sequence differences suggesting divergent evolution of this protein subfamily [10]. A previous report from 2008 demonstrated the existence of two distinct HSPA9B homologs in L. chagasi fortuitously isolated from an immunoscreening of a L. chagasi cDNA expression library [14] showing the same sequence arrangement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several heat-shock protein (HSP) chaperones and co-chaperones have been described in kinetoplastids and classified according to molecular mass as sHSP (small HSP), p23, Hsp40, Hsp60, Hsp70, Hsp90 and Hsp110 [ 10 15 ]. The sHSP family consists of heterogeneous members characterized by a molecular signature, the conserved α-crystallin domain (ACD), flanked by a variable N and C-terminal.…”
Section: Introductionmentioning
confidence: 99%